Prospective study of the changes in pharmacokinetics of immunosuppressive medications after laparoscopic sleeve gastrectomy. Issue 2 (13th October 2019) - Chan, Gabriel; Hajjar, Roy; Boutin, Lucie; Garneau, Pierre Y.; Pichette, Vincent; Lafrance, Jean‐Philippe; Elftouh, Naoual; Michaud, Josée; du Souich, Patrick
Abstract : Laparoscopic sleeve gastrectomy induces weight loss via the creation of a restrictive gastric tube for early satiety and is associated with an accelerated gastric transit time. A prospective, single‐dose pharmacokinetic study was performed, prior to and after laparoscopic sleeve gastrectomy, for tacrolimus, extended‐release tacrolimus, mycophenolate mofetil, and enteric‐coated mycophenolate sodium. The study included 12 morbidly obese patients in chronic renal failure. The median decrease in body mass index was 8.8 kg/m 2 with an excess body weight loss of 54.9%. The AUC24 of all drugs were increased after laparoscopic sleeve gastrectomy by 46%, 55%, 77%, and 74%, respectively. The maximum concentrations were increased for tacrolimus, extended‐release tacrolimus, and mycophenolate mofetil by 43%, 46%, and 65%. The apparent total clearances were decreased for tacrolimus, mycophenolate mofetil, and enteric‐coated mycophenolate sodium by 36%, 57%, and 38%. Laparoscopic sleeve gastrectomy can be associated with significant changes in pharmacokinetics of the drugs evaluated. The mechanism is likely decreased apparent drug clearance due to an increased drug exposure (from a more distal site of intestinal absorption with decreased intestinal metabolism), or decreased clearance (liver metabolism). Adapting the monitoring of immunosuppression will be important to avoid overdosing and potential side effects. Abstract : Laparoscopic sleeve gastrectomy, in addition to dramatic weight loss, results in significantly increased drug exposure and maximum concentration of oral immunosuppressive medications for morbidly obese kidney transplant candidates.